PENGARUH PENGGUNAAN MODEL COOPERATIVE INTEGRATED AND READING COMPOSITION TERHADAP KETERAMPILAN MENULIS SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SDN 85 SINGKAWANG - Susilawati; Liliyanti; Wahyuni Oktavia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) Determine the influence of writing skills of grade IV students after being given the Cooperative Integrated and Composition (CIRC) model at SDN 85 Singkawang. 2) To find out how much influence the writing skills of grade IV students are after being given the Cooperative Integrated and Composition (CIRC) model at SDN 85 Singkawang. The research used was an experimental research with a Post Test Only Control Group design. The population in this study is grade IV students of SDN 85 Singkawang. The research sample is taken by Purpose Sampling in this safe sampling to determine the sample with certain considerations. The prerequisite test carried out was a normality test using the Shapiro-Wilk formula and a variance homogeneity test was carried out to see the similarity of variants in both groups. Data were analyzed univariately with a significance level of 5% (0.05) for the first hypothesis test was used as an effect size test. The results of the study show that: 1) From the results of the calculation of short story writing skills of students in grade IV who use the Cooperative Integrated Reading and Composition (CIRC) model with classes that use the direct learning model in grade IV students of SDN 85 Singkawang. This is proven by the Independent Sample t-test. 2) The Cooperative Integrated Reading and Composition (CIRC) learning model has a great influence on writing skills in grade IV students of SDN 85 Singkawang. This is evidenced by the effect size test obtained a value of 1.125 with the high category using SPSS Version 26 obtained a sig (2-tailed) value < 0.05, which is 0.003 < 0.05.